PENERAPAN ANALISIS STANDAR BELANJA ALOKASI BELANJA KEGIATAN BIMBINGAN ATAU PELATIHAN TEKNIS PADA PEMERINTAH PROVINSI GORONTALO - , Iswan Hamzah, S.Pd. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study was conducted to decide a model of Standard Analysis of Expenses (ASB : Analisis Standar Belanja) to fulfill the normality of expensing budget in the guidance activity or technical training in the government of the province of Gorontalo, to calculate total budgets of the guidance activity and technical training according to the target of performance of 2010 based on ASB, and to assess the normality of the budget of the guidance or technical training in 2010 based on ASB. This study was implemented in the government of the province of Gorontalo using the method of research conducted by two approaches: library research and field research. The used data in this study was the secondary data, that was the document of implementation of budget of work unit in provincial equipment (DPA-SKPD : Dokumen Pelaksanaan Anggaran Satuan Kerja Perangkat Daerah) issued by the government of the province of Gorontalo, budgeting year of 2010. The study results showed that the ASB model developed to estimate the relationship total expenses and certain output or input ranges was good and has completed a model of linearity so it could be used as a predictor to decide the normality of expense in guidance activity or technical training in the government of the province of Gorontalo. Whereas, the resulted ASB model of the guidance activity or technical training was Y = 57.000.000 + 316.000X. The result of analysis of the normality of expense in 21 guidance activities or technical training showed that there were 13 activities experienced underfinancing and 8 activities experienced overfinancing. These showed that the conducted process of budgeting experienced oftenly surplus/minus of the normal expense number, so that it caused inefficiency of budget. In order to be used in the next year, ASB model needs to be customized, and by assumption of the inflation level in 2011 was 20 percent, it could be decided the fixed expense and the variable expense of the budgeting year of 2011: (1) fixed expenses of Rp68.400.000,- and (2) variable expenses of Rp379.000X (where X was expense control).